2023
DOI: 10.21203/rs.3.rs-2479953/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoscale reshaping of resonant dielectric microstructures by light-driven explosions

Abstract: Femtosecond-laser-assisted material restructuring employs extreme optical intensities to localize the ablation regions. To overcome the minimum feature size limit set by the wave nature of photons, there is a need for new approaches to tailored material processing at the nanoscale. Here, we report the formation of deeply-subwavelength features in silicon, enabled by localized laser-induced phase explosions in pre-fabricated silicon resonators. Using short trains of mid-infrared laser pulses, we demonstrate the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…More recently, Tokel et al interestingly demonstrated sub-surface 2D-confined nanochannel generation in c-Si by scanning micro-Bessel nanosecond laser beams at the vicinity of preformed structures [25]. While the nature of this pre-structure non-local seeding technique is associated with freedom limitations for 3D manufacturing applications, this represents an important advancement as it tends to translate in the bulk an important concept for nanoscale writing resolutions and exploited on surfaces [26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tokel et al interestingly demonstrated sub-surface 2D-confined nanochannel generation in c-Si by scanning micro-Bessel nanosecond laser beams at the vicinity of preformed structures [25]. While the nature of this pre-structure non-local seeding technique is associated with freedom limitations for 3D manufacturing applications, this represents an important advancement as it tends to translate in the bulk an important concept for nanoscale writing resolutions and exploited on surfaces [26].…”
Section: Introductionmentioning
confidence: 99%